Sachverständigenrat: Wie politiknah sollte die Beratung sein? - Christoph M. Schmidt; Benjamin Weigert; Ullrich Heilemann; Gebhard Kirchgässner; Tobias Thomas; Kees van Paridon (Wirtschaftsdienst, 2015)
Das Jahresgutachten des Sachverständigenrates für Wirtschaft 2014/15 wurde von der Politik teils heftig kritisiert, weil wichtige politische Entscheidungen infrage gestellt wurden. In Hinblick auf die monierten Einzelfragen gibt es auch aus der Wissenschaft Kritik. Der Sachverständigenrat selbst sieht hingegen seinen Auftrag nicht darin, die Regierung zu beraten, sondern sie kritisch und unabhängig zu begleiten. Seine Aufgaben sind nicht nur in der Politikberatung im engeren Sinne zu sehen, sondern auch in der Vermittlung von ökonomischen Problemstellungen in die Öffentlichkeit hinein. – – The German Council of Economic Experts (GCEE) has the legal mandate to independently assess the state of the German economy, to formulate its expert opinion regarding issues of economic policy and to alert readers to any undesirable developments which threaten to arise in this context. While this might not always be easily palatable for representatives from the political realm, the GCEE bases its analyses transparently on the current state of the economic literature and on empirical evidence to contribute to the formation of an informed judgement regarding economic policy issues among policy makers, economic actors and the general public. The GCEE's function is to offer advice to the government and provide information to the public. A survey of politicians and ministry officials shows that this advice is valued by the respondents. However, the members of the council are barely visible in the media and therefore contribute only minimally to the effective information of the broader public. One reason for this shortcoming is that fulfilling both duties is hardly possible from an institutional economics perspective. A useful comparison can be made with the the Netherlands, where the CPB, the Netherlands Bureau for Economic Policy Analysis - a government-financed but independent institution - has played a central role in forecasting economic developments and in analysing the consequences of policy changes in the Netherlands.
Keywords: A11; D78; 330; Politikberatung; Deutschland; Niederlande